(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Rheumatoid arthritis is a systemic autoimmune inflammatory disease having variable effects. Though RA occurs at any age, the most common age of onset of disease is 35 years and above, therefore predominantly affecting people of working age. Its prevalence is about 0.5% - 1% and steadily increases to 5% in women over the age of 70. RA is 2-3 times more common in females than males. About 350 million people are affected with RA worldwide. In U.S. nearly 40 million persons suffers are affiliated with RA, of these 60% are women. Traditionally, RA treatment was mostly symptomatic with main purpose to decrease the inflammation, pain and slow the progression of the disease. Allopathic drugs which are used normally for the treatment of RA are NSAIDs (Paracetamol, aspirin) and DMARDs (methotrexate, penicillamine, gold and azathioprine) and biologics. Though effective for acute treatment, the long term use of these drugs is self-limiting due to their serious adverse effects and they are relatively non-specific in their actions. Thus, plant-based therapeutic agents that not only slow down the disease progression with less/ no side effects but are also cost effective, continue to have scientific, social and commercial significance and appear to be gathering a momentum in health relevant areas.